1993
DOI: 10.1037/h0078791
|View full text |Cite
|
Sign up to set email alerts
|

Coping humour, stress, and cognitive appraisals.

Abstract: This study investigated relationships between sense of humour and cognitive appraisals and reappraisals of a potentially stressful event. Cognitive appraisals for an academic examination were obtained at several points in time. Consistent with our predictions, individuals with high scores on the Coping Humour scale appraised the exam as more of a positive challenge than did low humour individuals. In their reappraisals, high humour subjects' ratings of importance and positive challenge were positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
117
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(141 citation statements)
references
References 12 publications
6
117
0
10
Order By: Relevance
“…Martin (2001) correctly notes that results from studies investigating the stress-moderating effect of sense of humor have been inconsistent. However, it is worth noting that some of the studies in this domain have found a main effect of sense of humor, a direct negative relation between sense of humor and self-reported stress (e.g., Abel, 2002;Kuiper, Martin, & Olinger, 1993;Svebak, Götestam, & Jensen, 2004;Trice & Price-Greathouse, 1986). Moreover, Dixon's (1980) seminal analysis of the theoretical relation between humor and stress clearly indicates that there should be a main effect: Humor should reduce stress.…”
Section: Sense Of Humormentioning
confidence: 99%
“…Martin (2001) correctly notes that results from studies investigating the stress-moderating effect of sense of humor have been inconsistent. However, it is worth noting that some of the studies in this domain have found a main effect of sense of humor, a direct negative relation between sense of humor and self-reported stress (e.g., Abel, 2002;Kuiper, Martin, & Olinger, 1993;Svebak, Götestam, & Jensen, 2004;Trice & Price-Greathouse, 1986). Moreover, Dixon's (1980) seminal analysis of the theoretical relation between humor and stress clearly indicates that there should be a main effect: Humor should reduce stress.…”
Section: Sense Of Humormentioning
confidence: 99%
“…The current evidence implicates both types of strategies. On the intrapersonal side, women who are threatened with the stereotype that they are poor at math do not show typical performance deficits if they are high in coping sense of humor (Ford, Ferguson, Brooks, & Hagadone, 2004), suggesting that one manner of coping with stereotype threat is by using humor to reinterpret the situation as a challenge rather than a threat (see Kuiper, Martin, & Olinger, 1993). Stereotype threat has also been shown to lead to behavioral self-handicapping (reduced practice prior to a performance; Stone, 2002) as well as claimed self-handicapping (claiming external factors that disrupted performance; Keller, 2002), both of which could be employed for either intrapersonal or interpersonal purposes (see Arkin & Oleson, 1998).…”
mentioning
confidence: 99%
“…Desde este continuo fueron identificados dos estilos de humor positivos y dos negativos: (a) Humor de afiliación, características del individuos que dice cosas graciosas o chistes para facilitar las relaciones interpersonales de manera benigna; (b) autodesarrollo del humor o humor de mejora personal, involucra una mirada humorística de la vida para alegrarse uno mismo (Kuiper et al, 1993); c) humor agresivo, relacionado con el uso del sarcasmo, la ridiculez y de molestar a los otros para destacarse a costa de ellos; y (d) humor de auto-defensa descalificador personal o autodescalificador, centrado en la intención de divertir a otros mientras se auto ridiculiza (Martin et al, 2003). Evidencia sobre esta estructura del humor de cuatro dimensiones ha sido recabada en diferentes culturas y poblaciones: canadiense (Martin et al, 2003), argentina (Lillo, 2006), libanesa (Taher, Kazarian & Martin, 2008); italiana (Sirigatti, Penzo, Giannetti & Stefanile, 2014), austriaca y alemana (Stieger, Formann, & Burger, 2011), israelita (Zeigler-Hill & Besser, 2011, china (Yue et al, 2014;Zhao et al, 2012Zhao et al, , 2014, o taiwanesa (Chiang, Sheng, Wu, & Yen, 2014).…”
Section: Introductionunclassified